Tratamento eletroquímico de água produzida sintética para remoção de hidrocarbonetos policíclicos aromáticos - Pontes, Juliana Patrícia Souza Duarte (2014)
The aim of this work is the treatment of produced water from oil by using electrochemical technology. Produced water is a major waste generated during the process of exploration and production in the oil industry. Several approaches are being studied aiming at the treatment of this effluent; among them can be cited the biological process and chemical treatments such as advanced oxidation process and electrochemical treatments (electrooxidation, electroflotation, electrocoagulation, electrocoagulation). This work studies the application of electrochemical technology in the treatment of the synthetic produced water effluent through the action of the electron, in order to remove or transform the toxic and harmful substances from the environment by redox reactions in less toxic substances. For this reason, we used a synthetic wastewater, containing a mixture H2SO4 0,5M and 16 HPAs, which are: naphthalene, acenaphthylene, acenaphthene, fluorene, phenanthrene, anthracene, fluoranthene, pyrene, benzo (a) anthracene, chrysene, benzo(b)fluoranthene, benzo(k) fluoranthene, benzo(a)pyrene, indeno(1,2,3-cd)pyrene, dibenzo(a, h)anthracene, benzo(g, h, i)perylene. Bulk electrochemical oxidation experiments were performed using a batch electrochemical reactor containing a pair of parallel electrodes, coupled with a power supply using a magnetic stirrer for favoring the transfer mass control. As anodic material was used, a Dimensionally Stable Anode (DSA) of Ti/Pt, while as cathode was used a Ti electrode. Several samples were collected at specific times and after that, the analysis of these samples were carried out by using Gas Chromatography Coupled to Mass Spectrometry (GC - MS) in order to determine the percentage of removal. The results showed that it was possible to achieve the removal of HPAs about 80% (in some cases, more than 80%). In addition, as an indicator of the economic feasibility of electrochemical treatment the energy consumption was analyzed for each hour of electrolysis, and based on the value kWh charged by ANEEL, the costs were estimated. Thus, the treatment costs of this research were quite attractive